The Role of Institutions in Economic Growth: A Systematic Literature Review - Trpeski, Predrag; Tashevska, Biljana; Merdzan, Gunter (Josip Juraj Strossmayer University of Osijek, Faculty of Economics and Business, 2024)
Purpose: This paper gives a systematic literature review of the research field of institutions and economic growth. The goal of the paper is to provide information on predominant trends in publishing studies, prevailing sentiments on the role of institutions, and emerging themes in the field, to identify gaps in the existing literature and possible avenues for further research. Methodology: The study systematically reviews papers on institutions and economic growth from the Scopus database following the PRISMA protocol. The research uses descriptive analysis (annual distribution of articles, frequently referenced papers, central and emerging topics), sentiment analysis, and keyword co-occurrence network analysis. Results: A total number of 78 papers published between 2006 and 2023 were analysed. The results suggest a growing interest in the subject, encompassing topics such as governance, human capital, trade openness, and the resource curse. Sentiment analysis suggests that most of the literature is optimistic about the impact of institutions on fostering economic growth. Keyword analysis indicates that institutions, governance, and economic growth remain key areas of interest, with increasing emphasis on region-specific research and empirical approaches. Conclusion: The prevailing research indicates that quality institutions play a crucial role in economic growth, enhancing the impact of other factors like financial development, trade openness, and human capital. The review underscores the pivotal role of institutions in sustaining long-term economic progress and suggests further exploration of less researched areas, such as regional development and entrepreneurship, and the utilisation of additional scientific databases to deepen our comprehension of institutional dynamics.
Keywords: economic growth; institutions; systematic literature review